2004
DOI: 10.1023/b:biop.0000047150.82053.e9
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of CO<sub>2</sub> and O<sub>3</sub> on Antioxidative and Photoprotective Defense Systems in Needles of Ponderosa Pine

Abstract: Ponderosa pine (Pinus ponderosa Dougl. ex Laws.) seedlings were exposed to near ambient or elevated CO 2 (average concentrations during the last growing season 446 versus 699 µmol mol -1 ), combined with low or elevated O 3 for three seasons. Ozone exposure during the last growing season (accumulated dose above threshold 0.06 µmol mol -1 ) was 0.05 versus 26.13 µmol mol -1 h. Needles of the youngest age class were harvested after the dormancy period. Ozone exposure decreased needle contents of chlorophyll a, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
1
7
1
Order By: Relevance
“…Glutathione synthesis and its maintenance in the reduced form are essential factors of plant defence towards numerous forms of abiotic and biotic stress . Still, data on the total glutathione content under O 3 exposure is contradictory and ranges from no influence (Tausz et al, 2004 a) to an increase under O 3 exposure (Herbinger et al, 2005;Strohm et al, 2002). In the present study, expression profiles for Fsγ-ECS and FsGSHS showed neither an O 3 effect nor a significant difference between sun and shade leaves.…”
Section: Genes Connected With the Antioxidative Systemcontrasting
confidence: 86%
“…Glutathione synthesis and its maintenance in the reduced form are essential factors of plant defence towards numerous forms of abiotic and biotic stress . Still, data on the total glutathione content under O 3 exposure is contradictory and ranges from no influence (Tausz et al, 2004 a) to an increase under O 3 exposure (Herbinger et al, 2005;Strohm et al, 2002). In the present study, expression profiles for Fsγ-ECS and FsGSHS showed neither an O 3 effect nor a significant difference between sun and shade leaves.…”
Section: Genes Connected With the Antioxidative Systemcontrasting
confidence: 86%
“…2D), as the activity and concentration of ribulose-1,5-bisphosphate carboxylase/oxygenase or the regeneration of ribulose-1,5-bisphosphate might be depressed in the long term exposure to elevated CO 2 (Chen et al 2005;Drake et al 1997). It has been demonstrated that elevated CO 2 depressed chlorophyll content in conifer and broad-leaf tree species (Broadmeadow and Jackson 2000;Wustman et al 2001;Tausz et al 2004). This effect may be regarded as an adaptation to higher internal leaf CO 2 concentrations which decrease the need for more effective photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the most compelling reason for the protective role of elevated CO 2 is that it lowers O 3 flux into leaves by decreasing the stomatal conductance. Higher NADPH availability at elevated CO 2 is also a possible way to enhance antioxidative capability and reduce the detrimental effects of O 3 (Rao et al 1995), but studies on sugar maple (Niewiadomska et al 1999) and ponderosa pine (Tausz et al 2004) demonstrated that elevated CO 2 did not provide protection against O 3 phytotoxicity by enhancing antioxidative defense capacity.…”
mentioning
confidence: 99%
“…Results from this study demonstrate that photo‐protection from O 3 by elevated CO 2 also occurs during acute heat stress. Cellular anti‐oxidants play a key role in protecting plants from O 3 ‐related oxidative damage (Morre et al 1990; Willekens et al 1994), and CO 2 can have interactive effects with O 3 on anti‐oxidant production (Polle et al 1993; Azevedo et al 1998; Tausz et al 2004; Erice et al 2007). Our limited examination of anti‐oxidants in this study (i.e., catalase, Mn‐SOD, Cu/Zn‐SOD, carotenoids) suggests that the protective effects of elevated CO 2 from elevated O 3 during heat stress are not related to CO 2 ‐related increases in anti‐oxidants.…”
Section: Discussionmentioning
confidence: 99%